Fostering Religious Moderation in Pesantren: Cultivating Tolerance and Peace through Khilafiyah Fiqh in South Kalimantan’s Multicultural Context - Nadiyah, Nadiyah; Rahmi, Diana; Hafidzi, Anwar (Kawanua International Journal of Multicultural Studies, 2024)
Pesantren, traditional Islamic boarding schools in Indonesia, play a crucial role in fostering religious moderation and promoting tolerance and peace in multicultural contexts. This study explores the teaching of Khilafiyah Fiqh, or jurisprudential disagreement, in Pesantren in South Kalimantan and its impact on cultivating an inclusive and peaceful environment. The concept of khilafiyah, derived from the Islamic legal tradition, reflects the diversity of interpretations of Islamic law and is respected as a sign of dynamism and flexibility. Pesantren teach khilafiyah through various methods, including the recitation of classic Islamic texts, discussion, and debate, which encourage critical thinking and openness to different opinions. The implementation of khilafiyah fiqh in Pesantren involves teaching differences of opinion in various aspects of Islamic practice, such as prayer, zakat, and fasting. Kyai and Pesantren scholars emphasize the importance of respecting different views and avoiding fanaticism. Understanding khilafiyah has a positive impact on supporting religious moderation, as it encourages santri (students) to be inclusive and open to diversity, both within the Muslim community and in interfaith relations. Case studies in South Kalimantan demonstrate the successful application of khilafiyah fiqh in promoting tolerance and peace. However, challenges exist, including internal differences among teachers and santri, resistance to changes in traditional teaching methods, and external resistance from the community and other Islamic organizations. To overcome these challenges, Pesantren employ various approaches, including interfaith and cross-cultural dialogue, which strengthen the understanding of khilafiyah and its role in fostering a harmonious society.